The computer architecture course in a common core in computer science and engineer degrees - Proença, Alberto J. (Zielona Góra: Uniwersytet Zielonogórski)
The computer architecture subject is part of any course structure on computer related degrees at most Universities. A comprehensive curriculum spawns from computer structure and organisation to concurrent architectures, including performance evaluation. The approach to this subject - top-down, from programming techniques to hardware issues, or bottom-up, from digital systems to instruction sets - and its contents and duration, vary from course to course, and often from University to University.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka